Epidemiology of Cancer-Associated Thrombosis in Asia: A Systematic Review - Lee, Lai Heng; Nagarajan, Chandramouli; Tan, Chuen Wen; Ng, Heng Joo (Frontiers in Cardiovascular Medicine, 2021)
The epidemiology of cancer associated thrombosis (CAT) in Asia is less well-studied and differs from that in the western countries. Here, we systematically examine population based and hospital-based studies reported between 1995 and 2020 to understand the epidemiology of CAT in Asia. From population-based studies, the estimated incidence of VTE in cancer patients was 1.85–9.88 per 1,000 person-years. The incidence of CAT in Asia is significantly higher than non-cancer associated VTE in the general population and cancer is perhaps the most important risk factor for VTE. Hospital-based studies were heterogeneous in study designs and reveal a wide range of prevalence of VTE among cancer patients at 0.5–44.6% while the cancer prevalence rates among VTE patients ranged from 6.1 to 65.5%. The cancer sites most associated with VTE and risk factors were similar between Asian and Western studies. CAT has a major impact on the survival of patients with cancer in Asia, but thromboprophylaxis is not commonly practiced and validated risk assessment tools are lacking. This study highlights the urgent need for large multinational epidemiological studies in Asia to establish the true burden of CAT and to guide appropriate prevention strategies.